KAJIAN MAKANAN DALAM PERSPEKTIF ANTROPOLOGI - Yevita Nurti (Jurnal Antropologi: Isu-Isu Sosial Budaya, 2017)
This article is a literature study explain about the study of food, food habits and nutrition in the Anthropology perspective. The food and nutrition studies reviewed in this article only suggests some examples, which are considered popular and represent the themes in food discussion. The discussion starts from the beginning of anthropologist interest about food in culture until the process it.